1996
DOI: 10.1111/j.1467-9280.1996.tb00337.x
|View full text |Cite
|
Sign up to set email alerts
|

Repetition Blindness Interacts with Syntactic Grouping in Rapidly Presented Sentences

Abstract: This study tested for predicted effects of syntax on a repetition deficit (RD) known as repetition blindness, the reduced probability of recall for repeated words in rapid serial visual presentation (RSVP) sentences The syntactic variable was phrase-congruent versus phrase-incongruent grouping within simultaneous RSVP displays With phrase-congruent grouping, each RSVP display contained a syntactic phrase (e g, “to play sports” in the sentence “They wanted to play sports but sports were not allowed”), whereas w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 9 publications
1
16
1
Order By: Relevance
“…Because phrases are fundamentally syntactic/semantic entities, this finding is consistent with a role for semantic and syntactic factors in the RB paradigm, and supports the existence of SB. Results of Abrams et al (1996) Miller, in press; Miller & MacKay, in press) and is likewise consistent with the existence ofSB, with effects of semantic and syntactic factors on repetition deficits, and with the distributed memory approach to the relation between language and memory (see MacKay, in press).…”
Section: Phonological (Manejar) Formssupporting
confidence: 52%
See 1 more Smart Citation
“…Because phrases are fundamentally syntactic/semantic entities, this finding is consistent with a role for semantic and syntactic factors in the RB paradigm, and supports the existence of SB. Results of Abrams et al (1996) Miller, in press; Miller & MacKay, in press) and is likewise consistent with the existence ofSB, with effects of semantic and syntactic factors on repetition deficits, and with the distributed memory approach to the relation between language and memory (see MacKay, in press).…”
Section: Phonological (Manejar) Formssupporting
confidence: 52%
“…Contrary to this suggestion, however, Abrams, Dyer, and MacKay (1996) found that RB decreases rather than increases in magnitude when phrases appear within the same screen rather than word by word or broken up as in standard RSVP. In short, MacKay and Miller (1994) used appropriately controlled and conservative procedures for comparing the degree of SB and RB in their mixed-language sentences.…”
Section: Salience Ofrepeated Targetscontrasting
confidence: 47%
“…Abrams, Dyer, and MacKay (1996) have also demonstrated that RB is sensitive to the syntactic structure of sentences when words are presented in groups. However, this sensitivity to stimulus and task context is also compatible with Potter's (1999) elaboration of how CSTM influences the processes involved in converting activated types into structured tokens.…”
Section: Discussionmentioning
confidence: 99%
“…This is most clearly seen in RSVP sequences that, when read together, make a complete, coherent sentence only when the repeated word is detected, yet participants still consistently fail to report it (Bavelier, 1994;Bond & Andrews, 2008;Harris & Morris, 1998;Kanwisher, 1987;Kanwisher & Potter, 1990;Kanwisher & Potter, 1998;MacKay & Miller, 1994;Morris & Harris, 2002;. One exception to this was reported by Abrams, Dyer and MacKay (1996), who found that when sentences presented in an RSVP paradigm were either presented as syntactically correct phrases (e.g., "They wanted/to play sports/but sports/were not allowed") or syntactically incorrect phrases (e.g., "They wanted to/play sports but/sports were not/allowed"),…”
Section: Introductionmentioning
confidence: 80%
“…They hypothesize this kind of grouping is akin to that found for spoken words, arguing that RB likely exists for auditory stimuli, but is prevented by the phrase grouping that occurs with naturally spoken sentences (Abrams et al, 1996). Goldfarb & Treisman (2011);Kanwisher (1991); Kanwisher et al (1995) compared to those employing RSVP (Kanwisher, 1991;Luo & Caramazza, 1996).…”
Section: Introductionmentioning
confidence: 99%